THE CARBON SINK IN INTACT AMAZONIAN FORESTS IS AN OPPORTUNITY TO ACHIEVE SUSTAINABLE CONSERVATION - VICUÑA MIÑANO, Edgar (2018)
The primary intact forests of the Peruvian Amazon act as a carbon sink: a key ecosystem service of international importance. This sink has been quantified as 0.54 Mg C ha-1 year-1 (1990-2017) for the intact Amazonian forest in the protected areas and associated buffer zones of Peru. In other words, the conservation of intact forests in protected areas has helped to remove 9.6 million tonnes of carbon from the atmosphere per year, which is equivalent to approximately 85% of the emissions from fossil fuel combustion in Peru during 2012. It is necessary to include this carbon sink in the national inventory of greenhouse gas emissions for two reasons. Firstly, because it is a an important flux, it would help for estimating the carbon balance of Peru more accurately. Secondly, it would strengthen the need to maintain the integrity of these forests, for their role both as a stock and sink of carbon and for their biological diversity. The provision of this service as a sink can only be assured with effective and adaptive management of the protected areas of Peru. Reporting of this environmental service at a national level should be implemented through long-term monitoring of the carbon dynamics and impact of climate change on these forests via the RAINFOR (Amazon Forest Network) network of permanent forest plots and the MonANPeru project. The establishment of this monitoring system would allow the development of the finanancial mechanisms to close the funding gap and achieve sustainable conservation of the forests of the protected area network of Peru.